Force-induced unclonable label as well as preparation method and application thereof
By applying mechanical force and solvent drying to the photonic crystal hydrogel film, random spots are formed, and the solvent restriction and low spectral response sensitivity of existing photonic crystal hydrogel labels are solved, and a high intensity and stable spot is prepared. The force-impact non-clone label is suitable for optical encryption and anti-counterfeiting applications in the field of polymer materials.
Patent Information
- Application Number
- CN202411205886.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The existing photonic crystal hydrogels used in anti-counterfeiting labels have problems such as limited solvent conditions, low spectral response sensitivity, complex preparation process and unstable spot effect.
By applying mechanical force to the hydrogel film, the solvent volatilizes during the solvent drying process to form random spots, and the polymerization reaction is carried out using an emulsifier and an initiator to form electronegative polybutyl acrylate colloidal microspheres, combining acrylamide and ethylenedioxide. Monomers such as alcohol dimethacrylate were pressed and dried using patterned hollow steel templates to prepare non-clone labels.
It realizes the optical characteristics of high tensile and high intensity, randomly generates bright and stable light spots, significantly improving the encryption performance and usability of anti-counterfeiting labels, and is suitable for the fields of optical encryption anti-counterfeiting and rapid identification.
Smart Images

Figure HDA0005019010200000011 
Figure HDA0005019010200000012 
Figure HDA0005019010200000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a force-induced unclonable label and a preparation method and application thereof. Background Art
[0002] Photonic crystal structures are usually ordered structural materials formed by periodically alternating arrangement of two or more dielectric constants in a certain space. The structure also has periodic regulation on the refractive index of light, thus generating a photonic band gap (PHG). When the photonic band gap generated by a photonic crystal is within the visible light band, the visible light whose energy falls at the band gap cannot pass through the photonic crystal and is reflected, thereby forming coherent diffraction light on the surface of the photonic crystal, resulting in structural color on a macro scale. The photonic band gap is the main feature of a photonic crystal. We can control the propagation of light by regulating the photonic band gap, which provides an extremely important foundation for the development and breakthrough of new optical devices.
[0003] Responsive photonic crystals, whose light signals can be easily adjusted by external stimuli. By combining photonic crystal microspheres with stimulus-responsive materials, the structural color can be effectively tuned under external stimuli, laying the foundation for its application in anti-counterfeiting. Stimulus-responsive photonic crystals can be constructed in two ways: using responsive materials as the raw materials of photonic crystals; filling responsive materials into the gaps of assembled periodic structures to form composite materials. When external physical or chemical conditions change, responsive photonic crystals can respond to stimuli intelligently and generate changing light signals. Due to their adjustable structural colors and visual effects in response to various external stimuli, responsive photonic crystals have been widely used in advanced anti-counterfeiting.
[0004] The concept of PUF was first proposed by Ravikanth Pappu et al. in 2002, and was named physical one-way functions at the time. As a physical one-way function with inherent, unique and fingerprint-like characteristics, PUF is a unique key generated based on the inherent differences caused by uncontrollable variability and high randomness in the manufacturing process, even in the same manufacturing process. PUF is inherently difficult to copy, does not recognize compact mathematical representation and is tamper-proof. From the perspective of product security, the anti-counterfeiting and authentication hardware security technology developed based on PUF has the characteristics of low hardware resource occupancy, product identity information is not easy to leak, and product credentials are difficult to copy even after being captured, which greatly improves the security of product information authentication. At present, photonic crystals are combined with PUF to prepare physical unclonable anti-counterfeiting labels with stable structural colors, rainbow characteristics and more environmentally friendly. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the above-mentioned prior art photonic crystal hydrogels used for anti-counterfeiting, such as being able to be used only in the presence of solvents, having low spectral response sensitivity, having a complicated preparation process and having unstable light spot effects, the primary purpose of the present invention is to provide a method for preparing a force-induced unclonable label; this method applies mechanical force to the hydrogel film, and during the evaporation of the solvent, the solvent evaporates and elastically shrinks to form a random light spot.
[0006] Another object of the present invention is to provide a non-clonable tag prepared by the above preparation method.
[0007] Another object of the present invention is to provide an application of the above-mentioned unclonable label.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A method for preparing a non-cloneable tag comprises the following steps:
[0010] (1) adding an emulsifier to ultrapure water and stirring until dissolved, heating to 60° C., sequentially adding butyl acrylate, methacrylic acid and acrylamide, continuing stirring and heating to 78° C., dripping an aqueous solution of an initiator into the reaction system, and polymerizing at 78° C. for 8 to 10 hours to obtain an electronegative polybutyl acrylate colloidal microsphere emulsion;
[0011] (2) adding an emulsifier to the electronegative polybutyl acrylate colloidal microsphere emulsion obtained in step (1), adding an organic solvent to stir and dissolve, heating to 40° C., adding an oil-soluble monomer, wherein the oil-soluble monomer is isooctyl acrylate and / or isooctyl methacrylate, and stirring at 40° C. for 12 h; dialyzing the mixed solution in ultrapure water to separate unreacted polymer monomers to obtain a colloidal crystal emulsion;
[0012] (3) dissolving acrylamide, ethylene glycol dimethacrylate, N,N'-methylenebisacrylamide and polyethylene glycol diacrylate in the colloidal crystal emulsion obtained in step (2), adding an initiator 2-hydroxy-2-methylpropiophenone, and stirring the mixture in a dark environment to obtain a photonic crystal hydrogel precursor solution; subjecting the photonic crystal hydrogel precursor solution to polymerization reaction for 30 minutes under ultraviolet light conditions to obtain a structural color photonic crystal hydrogel film;
[0013] (4) Using a patterned hollow steel template to press the structural color photonic crystal hydrogel film obtained in step (3); clamping the template with clips on all sides and then placing it in an oven at 80° C. to dry for 8 hours to completely evaporate the solvent, thereby obtaining an unclonable label.
[0014] In step (1), the weight proportion of butyl acrylate is 8 to 15 parts, the weight proportion of methacrylic acid is 0.2 to 2 parts, the weight proportion of acrylamide is 0.1 to 0.5 parts, the weight proportion of emulsifier is 0 to 0.2 parts, and the weight proportion of ultrapure water is 60 to 150 parts; the aqueous solution of the initiator is a potassium persulfate aqueous solution with a mass percentage concentration of 5 to 50%, and the weight proportion of the aqueous solution of the initiator is 1 to 3 parts.
[0015] More preferably, in step (1), the weight proportion of butyl acrylate is 10 parts, the weight proportion of methacrylic acid is 1.7 parts, and the weight proportion of acrylamide is 0.3 parts; and the aqueous solution of the initiator is a potassium persulfate aqueous solution with a mass percentage concentration of 33%, and the weight proportion is 1 part.
[0016] The weight proportion of the emulsifier in step (2) is 0.02-0.03 parts; the weight proportions of the electronegative polybutyl acrylate colloidal microsphere emulsion, the organic solvent and the oil-soluble monomer are 6-9 parts, 1-4 parts and 0.2-1 parts respectively, preferably 8 parts, 2 parts and 0.8 parts. The organic solvent is anhydrous ethanol.
[0017] In step (3), the weight proportions of acrylamide, ethylene glycol dimethacrylate, N,N'methylenebisacrylamide, polyethylene glycol diacrylate and colloidal crystal emulsion are 0.5-2 parts, 0.1-0.5 parts, 0.02-0.6 parts, 0.01-0.1 parts and 0.2-0.8 parts, preferably 0.2 parts, 0.02 parts, 0.1 parts, 0.05 parts, 0.5 parts and 0.8 parts, respectively; the initiator is 2-hydroxy-2-methylpropiophenone; the total mass of acrylamide, ethylene glycol dimethacrylate, N,N'methylenebisacrylamide and polyethylene glycol diacrylate and the mass ratio of the initiator are 100:(0.5-2), preferably 100:1.
[0018] The emulsifier in step (1) or step (2) is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate; the particle size of the electronegative polybutyl acrylate colloidal microsphere emulsion obtained in step (1) is 130 to 230 nm.
[0019] The size of the patterned hollow steel template in step (4) is 1.5×1.5×0.1 mm.
[0020] The electronegative polybutyl acrylate colloidal microsphere emulsion in step (1) is any one or more of poly(butyl acrylate-methacrylic acid-acrylamide) nanospheres, poly(methyl methacrylate-butyl acrylate-acrylic acid) nanospheres, poly(styrene-butyl acrylate-methacrylic acid) nanospheres, poly(methyl methacrylate-methyl acrylate-acrylic acid) nanospheres, poly(styrene-acrylic acid) nanospheres, and poly(styrene-methyl methacrylate-methacrylic acid) nanospheres, preferably poly(butyl acrylate-methacrylic acid-acrylamide) nanospheres.
[0021] A force-induced unclonable label prepared by the above preparation method. The force-induced unclonable label is formed by polymer colloidal crystal microspheres as system cross-linking points, and a stable force-induced unclonable label with excellent spot effect is obtained after the solvent is completely evaporated.
[0022] The above-mentioned force-induced unclonable labels are used in the fields of optical encryption, anti-counterfeiting and rapid identification, force-induced sensors, and structural color regulation and patterning.
[0023] Principle of the present invention:
[0024] The non-clonable label of the present invention uses electronegative monodisperse polymer nanospheres as the building units of the microcrystalline region. The electronegative monodisperse polymer nanospheres self-assemble and construct microcrystalline light spots through the electrostatic action of the near electric field in the reaction system with the positively charged acrylamide monomer. In the self-assembly system of the monodisperse electronegative polymer nanospheres, there are intermolecular forces of repulsion and attraction between the electronegative polymer nanospheres, the acrylamide monomers, the crosslinking agent and the initiator. The film is pressed by mechanical force. During the solvent evaporation process, the mechanical force and the force of solvent evaporation act on the film together. Due to the different crosslinking degrees, the monodisperse polymer nanospheres shrink in the regions with different crosslinking degrees to form microcrystalline regions. These macroscopic and microscopic forces affect the regularity of the nano-micro arrangement, not only affecting the shape and formation position of the microcrystalline region, but also affecting the size of the microcrystalline region. After the solvent evaporates, random light spots of different colors and sizes are presented, which have high non-clonability and significantly improve the encryption performance and usability of the orientation material.
[0025] Compared with the prior art, the present invention has the following advantages and effects:
[0026] (1) In the preparation method of the present invention, during the hydrogel polymerization process, the oil-soluble monomers in the microspheres participate in the polymerization of the water-soluble monomers to form a polymer network structure that runs through the oil and water phases, thereby obtaining a strong interaction force between the microspheres and the base hydrogel, and achieving good mechanical properties of high tensile strength and high strength.
[0027] (2) The preparation method of the present invention has a simple process and mild and controllable conditions, and can produce high-strength photonic crystal hydrogel materials with excellent optical properties and stretchability, which is suitable for promotion and application in the field of polymer materials.
[0028] (3) The high-strength photonic crystal hydrogel prepared by the present invention has the optical property of mechanochromism and randomly generates bright and stable light spots, which can be applied to optical encryption and anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are scanning electron microscope images of the unclonable tags of Examples 1 to 3, wherein a to c are surface morphology images of Examples 1 to 3 at different magnifications under a scanning electron microscope.
[0030] Figure 2 Figures 1 and 2 are atomic force microscope images of the unclonable tags of Examples 1 to 3, wherein Figure a is a surface morphology image of Example 1, Figure c is an atomic force microscope morphology image of the junction of red and green light spots, Figure b is a locally enlarged atomic force microscope morphology image of the red light spot, and Figure d is a locally enlarged atomic force microscope morphology image of the green light spot.
[0031] Figure 3 These are magnified light spot microscope images of the unclonable labels of Examples 1 to 3 in a completely dry state, wherein a to c are circular patterns on the unclonable labels, and d to f are U-shaped patterns on the unclonable labels.
[0032] Figure 4 These are the reflection spectra of the unclonable labels of Examples 1 to 3.
[0033] Figure 5 The stress-strain curves of the unclonable tags induced by Examples 1 to 3 are shown.
[0034] Figure 6 These are different patternings of the force-induced unclonable tags of Examples 1 to 3, where a and d are structural color photonic crystal hydrogel films obtained under UV polymerization, b and e are two patterned force-induced unclonable tags with the solvent completely evaporated, and c and f are corresponding partial enlarged views. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to specific embodiments, but they should not be construed as limiting the present invention.
[0036] The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are commercially available reagents and materials unless otherwise specified.
[0037] The parts in the following examples are all parts by weight.
[0038] Example 1
[0039] A method for preparing a non-clonable tag comprises the following steps:
[0040] (1) Preparation of poly(butyl acrylate-methacrylic acid-acrylamide) nanospheres: Weigh 0.012 parts of sodium dodecyl sulfate and add it to 150 parts of deionized water, stir and dissolve. Set the stirring speed to 2000 r / min, introduce inert gas for 30 min, heat to 60°C, add 15 parts of butyl acrylate, 1.5 parts of methacrylic acid and 0.5 parts of acrylamide in sequence, continue heating and stirring to 78°C, add 1 part of 33% potassium persulfate aqueous solution, maintain 78°C and stir evenly for 8 hours to obtain the poly(butyl acrylate-methacrylic acid-acrylamide) nanosphere polymer, which is the electronegative polybutyl acrylate colloidal microsphere emulsion.
[0041] (2) adding 0.025 parts of sodium dodecyl sulfate to a mixture of 10 parts of the electronegative polybutyl acrylate colloidal microsphere emulsion prepared in step (1) and 1.5 parts of anhydrous ethanol and stirring to dissolve, setting the stirring speed to 800 r / min, heating to 40° C. and adding 0.9 parts of isooctyl acrylate, maintaining 40° C. and stirring uniformly for 12 hours; dialyzing the obtained solution in deionized water for 48 hours to remove organic solvents and small molecules, and obtaining an oil-soluble monomer swollen colloidal crystal emulsion with a diameter of 180 nm;
[0042] (3) Weigh 0.5 parts of acrylamide and dissolve it in 0.56 parts of the colloidal crystal emulsion prepared in step (2), then add 0.02 parts of ethylene glycol dimethacrylate, 0.02 parts of N,N'methylenebisacrylamide and 0.1 parts of polyethylene glycol diacrylate, and add 0.0015 parts of initiator 2-hydroxy-2-methylpropiophenone, stir well under light-proof conditions, and obtain a photonic crystal hydrogel precursor solution; inject the precursor solution into a sandwich mold with a spacing of 0.5 mm, polymerize under ultraviolet light for 30 minutes, and obtain a structural color photonic crystal hydrogel film after demolding;
[0043] (4) Using a patterned hollow steel template (size: 1.5×1.5×0.1 mm) to press the structural color photonic crystal hydrogel film obtained in step (3); clamping the template with clips on all sides and drying it in an oven at 80° C. for 8 h to completely evaporate the solvent, thereby obtaining an unclonable tag.
[0044] Example 2
[0045] A method for preparing a non-clonable tag comprises the following steps:
[0046] (1) Preparation of poly(butyl acrylate-methacrylic acid) nanospheres: Weigh 0.01 parts of sodium dodecyl sulfate and add it to 80 parts of deionized water and 25 parts of anhydrous ethanol, stir and dissolve. Set the stirring speed to 2000 r / min, introduce inert gas for 30 min, heat to 60°C, add 10 parts of butyl acrylate and 1 part of methacrylic acid in sequence, continue heating and stirring to 78°C, add 1 part of 33% potassium persulfate aqueous solution, maintain 78°C and stir evenly for 8 h to obtain a polymer colloidal crystal emulsion.
[0047] (2) adding 0.025 parts of sodium dodecyl sulfate to a mixture of 10 parts of the electronegative polybutyl acrylate colloidal microsphere emulsion prepared in step (1) and 1.5 parts of anhydrous ethanol and stirring to dissolve, the stirring speed of the facility is 800 r / min, heating to 40° C., adding 0.9 parts of isooctyl acrylate, and maintaining 40° C. and stirring uniformly for 12 hours; then dialyzing the obtained solution in deionized water for 48 hours to remove organic solvents and small molecules, and obtaining an oil-soluble monomer swollen colloidal crystal emulsion with a diameter of 210 nm;
[0048] (3) Weigh 0.1 part of acrylamide and dissolve it in 0.56 part of the colloidal crystal emulsion prepared in step (2), then add 0.02 part of ethylene glycol dimethacrylate, 0.01 part of N,N'methylenebisacrylamide and 0.02 part of polyethylene glycol diacrylate, and add 0.0015 part of initiator 2-hydroxy-2-methylpropiophenone, stir well under light-proof conditions, and obtain a photonic crystal hydrogel precursor solution; inject the precursor solution into a sandwich mold with a spacing of 0.5 mm, polymerize under ultraviolet light for 30 minutes, and obtain a structural color photonic crystal hydrogel film after demolding;
[0049] (4) Using a patterned hollow steel template (size: 1.5×1.5×0.1 mm) to press the structural color photonic crystal hydrogel film obtained in step (3); clamping the template with clips on all sides and drying it in an oven at 80° C. for 8 h to completely evaporate the solvent, thereby obtaining an unclonable tag.
[0050] Example 3
[0051] (1) Preparation of poly(methyl methacrylate-butyl acrylate) nanospheres: Weigh 0.05 parts of sodium dodecyl sulfate and add it to 60 parts of deionized water, stir and dissolve. Set the stirring speed to 1000 r / min, introduce inert gas for 30 min, heat to 60°C, add 3.5 parts of methyl methacrylate and 3.5 parts of butyl acrylate in sequence, continue heating and stirring to 78°C, add 1 part of 33% potassium persulfate aqueous solution, maintain 78°C and stir evenly for 12 h to obtain a polymer colloidal crystal emulsion.
[0052] (2) adding 0.03 parts of sodium dodecyl sulfate to a mixture of 12 parts of electronegative polybutyl acrylate colloidal microspheres prepared in step (1) and 1.5 parts of anhydrous ethanol and stirring to dissolve, the stirring speed of the facility is 800 r / min, heating to 40° C., adding 0.9 parts of isooctyl acrylate, and maintaining 40° C. and stirring uniformly for 12 hours; dialyzing the obtained solution in deionized water for 48 hours to remove organic solvents and small molecules, and obtaining an oil-soluble monomer swollen colloidal crystal emulsion with a diameter of 200 nm;
[0053] (3) Weigh 0.05 parts of acrylamide and dissolve it in 0.56 parts of the colloidal crystal emulsion prepared in step (2), then add 0.02 parts of ethylene glycol dimethacrylate, 0.01 parts of N,N'methylenebisacrylamide and 0.02 parts of polyethylene glycol diacrylate, and add 0.0015 parts of initiator 2-hydroxy-2-methylpropiophenone, stir well under light-proof conditions, and obtain a photonic crystal hydrogel precursor solution; inject the precursor solution into a sandwich mold with a spacing of 0.5 mm, polymerize under ultraviolet light for 30 minutes, and obtain a structural color photonic crystal hydrogel film after demolding;
[0054] (4) Using a patterned hollow steel template (size: 1.5×1.5×0.1 mm), the structural color photonic crystal hydrogel film obtained in step (3) was pressed, fixed with clips on all sides, placed in an oven at 80° C., dried for 8 h, and then demolded to obtain an unclonable label.
[0055] Comparative Example 1
[0056] (1) Preparation of poly(polystyrene-methacrylic acid) nanospheres: Weigh 0.012 parts of sodium dodecyl sulfate and add it to 85 parts of deionized water, stirring and dissolving. Set the stirring speed to 2000 r / min, introduce inert gas for 30 min, heat to 60°C, add 15 parts of styrene and 1.5 parts of methacrylic acid in sequence, continue heating and stirring to 78°C, add 0.1 parts of 33% potassium persulfate aqueous solution, maintain 78°C and stir evenly for 8 h to obtain a polymer colloidal crystal emulsion.
[0057] (2) Weigh 0.5 parts of acrylamide and dissolve it in 0.56 parts of the electronegative polybutyl acrylate colloidal microsphere emulsion prepared in step (2), then add 0.02 parts of ethylene glycol dimethacrylate, 0.01 parts of N,N'methylenebisacrylamide and 0.02 parts of polyethylene glycol diacrylate, and add 0.0015 parts of initiator 2-hydroxy-2-methylpropiophenone and stir well under light-proof conditions to obtain a photonic crystal hydrogel precursor solution; inject the precursor solution into a sandwich mold with a spacing of 0.5 mm, polymerize under ultraviolet light for 30 minutes, and obtain a structural color photonic crystal hydrogel film after demolding;
[0058] (3) Using a patterned hollow steel template (size: 1.5×1.5×0.1 mm) to press the structural color photonic crystal hydrogel film obtained in step (2); clamping the template with clips on all sides and drying it in an oven at 80° C. for 8 h to completely evaporate the solvent, thereby obtaining an unclonable tag.
[0059] Test Example 1
[0060] 1. Scanning electron microscopy
[0061] Experimental steps: The non-clonable labels of Examples 1 to 3 were fractured with liquid nitrogen and attached to an electron microscope table with conductive adhesive, dried in an oven at 80°C for 12 hours, and finally the microscopic morphology of the labels was observed under a field emission scanning electron microscope (magnification 20K).
[0062] Result analysis: The surface morphology of the unclonable tags of Examples 1 to 3 is as follows: Figure 1 .like Figure 1 It can be seen that the microspheres in the unclonable medium have regular morphology, uniform particle size and neat arrangement.
[0063] 2. Atomic force microscopy
[0064] Experimental steps: The force-free cloning labels of Examples 1 to 3 were dried in an oven at 80° C., cut into appropriate sizes and pasted on a glass sheet, and finally the microscopic morphology of the labels was observed under an atomic force microscope.
[0065] Result analysis: The microscopic morphology of the force-induced unclonable labels of Examples 1 to 3 was taken using an atomic force microscope as shown in the figure. Figure 2 It can be seen that the microspheres in the non-clonable force have regular morphology, uniform particle size, and are neatly arranged. Figure 2 It can be seen that due to the mechanical force, the unclonable label produces light spots of different colors. Through the Bragg derivative formula, it is obtained that the distance between the microspheres corresponds to their colors.
[0066] 3. Light spot effect diagram
[0067] Experimental steps: The completely dried non-cloneable labels of Examples 1 to 3 were placed under an optical microscope, and photographed and stored under the irradiation of a 45° beam.
[0068] Result analysis: The unclonable labels obtained in Examples 1 to 3 were photographed using an optical microscope. Figure 3 shown. Figure 3 These are the non-clonable tags prepared in Examples 1 to 3. Figure 3 It can be seen that in Examples 1 to 3, mechanical force is applied to the polymer film, and after the solvent is evaporated, light spots of different colors appear, and the light spots of the prepared force-induced unclonable labels have uniform sizes.
[0069] 4. Reflection spectrum test
[0070] Experimental steps: Place the unclonable tag of Example 1 on a sample stage and use a high-tech spectral camera for testing.
[0071] Result analysis: The reflectance spectrum of the non-clonable tag of Example 1 is as follows: Figure 4 As shown. Under the condition of keeping the Lizhi unclonable label completely dry, reflection peaks of different wavelengths can be measured at different positions in a sample, proving that different positions in the Lizhi unclonable label have different colors. The disordered light spot pattern gives the photonic crystal film anti-counterfeiting label the property of being unclonable, and combined with artificial intelligence, the anti-counterfeiting label can be identified and read.
[0072] 5. Universal testing machine
[0073] Experimental steps: Place the force-induced unclonable label of Example 1 on a universal testing machine and use the universal testing machine to perform a test.
[0074] Result analysis: The stress-strain curve of the force-induced unclonable tag in Example 1 is as follows: Figure 5 As shown in the figure, under the condition that the non-clonable label is kept completely dry, the sample has certain mechanical properties and can be used in a variety of environments and scenarios.
[0075] 6. Patterned effect diagram
[0076] Experimental steps: The undried and completely dried non-cloneable labels of Examples 1 to 3 were placed under an optical microscope, and photographed and stored under the irradiation of a 45° beam.
[0077] Result analysis: The formation process of the unclonable tag obtained in Examples 1 to 3 was photographed using an optical microscope. The photographs obtained are as follows: Figure 6 As shown in the figure. Figures a and d are structural color photonic crystal hydrogel films obtained under UV polymerization, Figures b and e are two patterned force-induced unclonable tags with the solvent completely evaporated under the action of mechanical force, and Figures c and f are the corresponding partial enlarged images. It can be seen that under the continuous action of mechanical force, the force-induced unclonable tags produce random multi-color spots after the solvent evaporates.
[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a non-clonable tag, characterized in that The steps include: (1) adding an emulsifier to ultrapure water and stirring until dissolved, heating to 60° C., sequentially adding butyl acrylate, methacrylic acid and acrylamide, continuing stirring and heating to 78° C., dripping an aqueous solution of an initiator into the reaction system, and polymerizing at 78° C. for 8 to 10 hours to obtain an electronegative polybutyl acrylate colloidal microsphere emulsion; (2) adding an emulsifier to the electronegative polybutyl acrylate colloidal microsphere emulsion obtained in step (1), adding an organic solvent to stir and dissolve, heating to 40° C., adding an oil-soluble monomer, wherein the oil-soluble monomer is isooctyl acrylate and / or isooctyl methacrylate, and stirring at 40° C. for 12 h; dialyzing the mixed solution in ultrapure water to separate unreacted polymer monomers to obtain a colloidal crystal emulsion; (3) dissolving acrylamide, ethylene glycol dimethacrylate, N,N'-methylenebisacrylamide and polyethylene glycol diacrylate in the colloidal crystal emulsion obtained in step (2), adding an initiator 2-hydroxy-2-methylpropiophenone, and stirring the mixture in a dark environment to obtain a photonic crystal hydrogel precursor solution; subjecting the photonic crystal hydrogel precursor solution to polymerization reaction for 30 minutes under ultraviolet light conditions to obtain a structural color photonic crystal hydrogel film; (4) Using a patterned hollow steel template to press the structural color photonic crystal hydrogel film obtained in step (3); clamping the template with clips on all sides and then placing it in an oven at 80° C. to dry for 8 hours to completely evaporate the solvent, thereby obtaining an unclonable label.
2. The method for preparing a non-clonable label according to claim 1, characterized in that: In step (1), the weight proportion of butyl acrylate is 8 to 15 parts, the weight proportion of methacrylic acid is 0.2 to 2 parts, the weight proportion of acrylamide is 0.1 to 0.5 parts, the weight proportion of emulsifier is 0 to 0.2 parts, and the weight proportion of ultrapure water is 60 to 150 parts; the aqueous solution of the initiator is a potassium persulfate aqueous solution with a mass percentage concentration of 5 to 50%, and the weight proportion of the aqueous solution of the initiator is 1 to 3 parts.
3. The method for preparing a non-clonable label according to claim 1, characterized in that: The weight proportion of the emulsifier in step (2) is 0.02-0.03 parts; the weight proportions of the electronegative polybutyl acrylate colloidal microsphere emulsion, the organic solvent and the oil-soluble monomer are 6-9 parts, 1-4 parts and 0.2-1 parts respectively.
4. The method for preparing a non-clonable label according to claim 1, characterized in that: In step (3), the weight proportions of acrylamide, ethylene glycol dimethacrylate, N,N'methylenebisacrylamide, polyethylene glycol diacrylate and colloidal crystal emulsion are 0.5-2 parts, 0.1-0.5 parts, 0.02-0.6 parts, 0.01-0.1 parts and 0.2-0.8 parts respectively; the initiator is 2-hydroxy-2-methylpropiophenone; the total mass of acrylamide, ethylene glycol dimethacrylate, N,N'methylenebisacrylamide and polyethylene glycol diacrylate and the mass ratio of the initiator are 100:(0.5-2).
5. The method for preparing a non-clonable label according to claim 1, characterized in that: The emulsifier in step (1) or step (2) is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate; the particle size of the electronegative polybutyl acrylate colloidal microsphere emulsion obtained in step (1) is 130 to 230 nm.
6. The method for preparing a non-clonable tag according to claim 1, characterized in that: The size of the patterned hollow steel template in step (4) is 1.5×1.5×0.1 mm.
7. The method for preparing a non-clonable tag according to claim 1, characterized in that: The electronegative polybutyl acrylate colloidal microsphere emulsion in step (1) is any one or more of poly(butyl acrylate-methacrylic acid-acrylamide) nanospheres, poly(methyl methacrylate-butyl acrylate-acrylic acid) nanospheres, poly(styrene-butyl acrylate-methacrylic acid) nanospheres, poly(methyl methacrylate-methyl acrylate-acrylic acid) nanospheres, poly(styrene-acrylic acid) nanospheres, and poly(styrene-methyl methacrylate-methacrylic acid) nanospheres.
8. A non-clonable tag prepared by the preparation method according to any one of claims 1 to 7.
9. Application of the force-induced unclonable label according to claim 8 in the fields of optical encryption anti-counterfeiting and rapid identification, force-induced sensor, and structural color regulation and patterning.
Citation Information
Patent Citations
High-strength photonic crystal hydrogel, preparation method and application thereof
CN110041464A
Unclonable anti-counterfeiting material based on nanosphere self-assembly as well as preparation method and application of unclonable anti-counterfeiting material
CN113621110A
Cited By
Preparation method and application of liquid colloidal crystal film material
CN120163094A
Preparation method and application of liquid colloidal crystal thin film materials
CN120163094B